Analisis Strategi Bisnis Dalam Meningkatkan Daya Saing Pt. Srijaya Ciptagraha - Aninda Harapan (Universitas Tarumanagara, 2019)
To embrace a competitive world, PT. Srijaya Ciptagraha should understand the strength and the weakness of their company and see the opportunities and threats come from the market so they can implement strategy that will increase it’s competitive power so they can gain more profit. The purpose of this research: 1) to identify the internal and external factor of PT. Srijaya Ciptagraha, 2) to provide a business strategy recommendation for PT. Srijaya Ciptagraha to increase their competitive advantages. The method that used in this research is Descriptive Research. From the QSPM Matrix Analysis of PT. Srijaya Ciptagraha, market penetration stratey placed in the 1st place with the attractiveness score is 6.393. This score is higher compare to the product development which ranked 2nd place, 5.178 and market development which ranked 3rd place with the score 4.741. This shows that the alternative strategy that needs to implement in PT. Srijaya Ciptagraha to increase their competitive advantages is Market Penetration Strategy.